HUMAN RESOURCES MANAGEMENT BASED ON ISLAM AND WESTERN VIEW - Indra Gunawan, Cakti (Book of Open Source (BOS), 2024)
This book focussed on human resources management based on Islam and Western view since the area study of human resources management in the Islamic countries (especially in Indonesia with the majority of the population is Muslim) has significantly increase. Therefore, it is the interesting research area for the students and researchers who learn this area. In the last decade, Islam consistent with the negative issue of terrorism and other negative prospensity. We know that the western scientist already published a thousand books about human resources management since the emergence of the industrial revolution until nowadays. However, the literature of human resources management based on Islam is still slight. Based on this argumentation, the writer bound the knowledge of many sources from the Al-Quran and Al-Hadits and another prophet Mohammad perspective to create a special issue of the human resources management based on Islam and try to compare the potential perspective of the westernscientist